2015
DOI: 10.1590/s1413-65382115000300004
|View full text |Cite
|
Sign up to set email alerts
|

O Trabalho do Professor, Indicadores de Burnout, Práticas Educativas e Comportamento dos Alunos: Correlação e Predição

Abstract: RESUMOA ocorrência do burnoutem professores pode afetar também suas práticas educativas, seu repertório de habilidades sociais e o comportamento de alunos. Na literatura tais variáveis são abordadas de forma independente, o que dificulta sua compreensão. Este estudo teve como objetivos correlacionar e predizer as variáveis: condições de trabalho do professor, indicadores deburnout, práticas educativas do professor e o repertório de habilidades sociais e de problemas de comportamento dos alunos. Participaram 94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
5
0
4
Order By: Relevance
“…En las variables laborales, una investigación señaló que a mayor antigüedad en la experiencia docente mayor realización personal y profesional y a menor antigüedad mayor despersonalización y agotamiento emocional (62) . Así también, los elevados niveles de SB se asociaron a las variables condiciones inadecuadas de salud (54) , ausentismo laboral (5) , relaciones interpersonales desfavorables (47) y percepción negativa de las condiciones del lugar de trabajo, las características y las demandas de la tarea (25,39,41,42,45,50,51,74,75) .…”
Section: Objetivos Y Principales Resultados De Los Estudiosunclassified
See 1 more Smart Citation
“…En las variables laborales, una investigación señaló que a mayor antigüedad en la experiencia docente mayor realización personal y profesional y a menor antigüedad mayor despersonalización y agotamiento emocional (62) . Así también, los elevados niveles de SB se asociaron a las variables condiciones inadecuadas de salud (54) , ausentismo laboral (5) , relaciones interpersonales desfavorables (47) y percepción negativa de las condiciones del lugar de trabajo, las características y las demandas de la tarea (25,39,41,42,45,50,51,74,75) .…”
Section: Objetivos Y Principales Resultados De Los Estudiosunclassified
“…Es importante mencionar que existen diferentes variables individuales como el sexo, edad, estado civil, nivel de estudios, composición familiar, habilidades sociales, estilos de afrontamiento frente al estrés, tolerancia al fracaso y a la frustración, entre otras (10,(22)(23)(24)(25) ; y variables sociales, intralaborales y extralaborales, incluyendo escaso apoyo social, multiplicidad de tareas, espacios inadecuados, falta de tiempo y remuneración insuficiente, clima organizacional y relaciones sociales laborales inadecuadas, etc., las cuales constituyen factores de riesgo que incrementan la probabilidad del sujeto de presentar SB (10,(22)(23)(24)(25) .…”
Section: Introductionunclassified
“…The literature has confirmed over the years the role of variables related to the perception of the worker, such as workload (Galindo et al, 2012;Lima et al, 2013;Novais et al, 2016;Rodrigues & Carlotto, 2017;Silva et al, 2015;Tironi et al, 2016), organizational support (Lorenz & Guirardello, 2014), autonomy (Rodriguez & Carlotto, 2017), recognition at work (Prestes et al, 2015;Zanatta & Lucca, 2015), and working conditions (Silva, Bolsoni-Silva, Rodrigues, & Capellini, 2015) in the prediction of BS. Although certain socio-demographic and individual variables such as sex (Carlotto, 2011), age (Esteves-Ferreira, Santos & Rigolon, 2014;Koga, et al, 2015), and marital status (Zanatta & Lucca, 2015), among others, have indicated a relation to BS in the explanatory models, they generally have low predictive power, (Maslach, Schaufeli, & Leiter, 2001;Queirós, Carlotto, Kaiseler, Dias, & Pereira, 2013;Sticca & Scotton, 2019) when compared to work-related variables, which points to the importance of the design and characteristic of the work context as determinants of the occurrence of BS (Maslach & Leiter, 2016 a).…”
mentioning
confidence: 93%
“…In addition, schools today face difficult challenges, such as the absence of public policies and archaic didactic-pedagogical work that undermine the continuing education of educators and the promotion of socio-emotional and academic competences that are essential for students' learning and permanence in school (Dazzani et al, 2014;Silva, Bolsoni-Silva, Rodrigues, & Capellini, 2015). Thus, it is not uncommon for teachers to be one step away from stress or Burnout Syndrome.…”
mentioning
confidence: 99%
“…Burnout syndrome is one of the main causes of teachers' leave of absence from work and can lead to medium-and long-term damage to the physical and mental health of educators (Dieh & Marin, 2016). In addition, several studies indicate that Burnout not only reduces teachers' awareness of their personal and professional competencies, but also negatively impacts the relationship with their students (Achkar, Leme, Soares, & Yunes, 2016;Koga et al, 2015;Silva et al, 2015). Thus, the Burnout Syndrome is a risk factor for the healthy development of both teachers and students and it hinders the expression of resilience processes in the school context.…”
mentioning
confidence: 99%